1995
DOI: 10.1111/j.1365-2958.1995.mmi_17020379.x
|View full text |Cite
|
Sign up to set email alerts
|

The leucine zipper of Aeromonas salmonicida AbcA is required for the transcriptional activation of the P2 promoter of the surface‐layer structural gene, vapA, in Escherichia coli

Abstract: The Aeromonas salmonicida AbcA protein is involved in the synthesis of the O-polysaccharide side-chains on the lipopolysaccharide and is also capable of enhancing the expression of the structural gene for the A-layer, vapA, when cloned into Escherichia coli. The P2 promoter of the vapA gene of A. salmonicida was cloned into a promoter probe vector and expression in E. coli was monitored. The expression of P2::lacZ was shown to be increased when abcA was provided in trans. AbcA contains an N-terminal ATP-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A recent study has determined that this activation of vapA expression in E. coli occurs at the level of transcription A. SALMONICIDA PATHOGENESIS (Noonan & Trust, 1995b). The abcA alleles which had single base mutations in the ATP-binding domain a#ecting O-chain synthesis and secretion, were still able to increase the expression of the vapA gene.…”
Section: An a Salmonicida Gene Involved In O-polysaccharide Secmentioning
confidence: 98%
“…A recent study has determined that this activation of vapA expression in E. coli occurs at the level of transcription A. SALMONICIDA PATHOGENESIS (Noonan & Trust, 1995b). The abcA alleles which had single base mutations in the ATP-binding domain a#ecting O-chain synthesis and secretion, were still able to increase the expression of the vapA gene.…”
Section: An a Salmonicida Gene Involved In O-polysaccharide Secmentioning
confidence: 98%
“…Further, it could be demonstrated that AbcA is a bifunctional protein in which the Nterminal part regulates the synthesis of the O-polysaccharide side chains of the LPS, functioning as a binding site for the VapA protein. The C-terminal leucine zipper increases expression of the vapA gene and can thus be considered as a transcriptional activator of the P2 promoter (25,95,96).…”
Section: S-layer Proteins and Genesmentioning
confidence: 99%
“…This bacterium produces homogenous (nonmodal) O-PS chain lengths (22), and the NBD protein (AbcA) is required for O-PS export (24). AbcA also contains an extended C-terminal domain that contains a putative leucine zipper, which is not essential for O-PS export but is required for proper transcription of the surface layer protein gene vapA (25,100). Conversely, the activity of the core NBD portion of AbcA is confined to O-PS export.…”
Section: Variations On the Theme-diversity In Function Of Extended C-mentioning
confidence: 99%